Vegetation dynamics in north-western Mediterranean regions: Instability of the Mediterranean bioclimate - De Beaulieu, J.-L.; Miras, Y.; Andrieu-Ponel, V.; Guiter, F. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract Pollen and plant macrofossil records from a selection of sites in Spain, France and Italy are used to explore the origin and the development of the Mediterranean vegetation. The role of evergreen and summergreen taxa is discussed. The expansion of sclerophyllous trees during the Pleistocene interglacials is well correlated with the orbital forcing. During the Holocene, the large number of data illustrates latitudinal and longitudinal differences in vegetation dynamics. Multidisciplinary studies identify short terms climatic fluctuations. The debate is still open between those who attribute an increase of sclerophyllous forests during the late Holocene to a trend toward aridity and those who consider this dynamic as human-induced.
doi: 10.1080/11263500500197858doi: 10.1080/11263500500197858The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: human impact; Mediterranean ecosystems; palaeoclimates; palynology; review